Pengembangan Media Pembelajaran Big Book Perjalanan Menuju Pancasila untuk Meningkatkan Pemahaman Sejarah Pancasila Siswa Kelas 3 Sekolah Dasar - Regina Sarudi; Susan Noviaty Herienth Jacobus (Departement of Mathematics Education, 2024)
The Indonesian people will face many problems, one of which is a lack of understanding of the history of the birth of Pancasila. This research aims to develop Big Book learning media that is simple and easy for students to understand about the history of the birth of Pancasila. This research uses R&D (Research and Development). The development model applies 4 stages: 1) Define, 2) Design, 3) Develop, 4) Disseminate. The data collection techniques used are questionnaires, documentation and tests. Then, the data was analyzed through quantitative and qualitative data. As a result, 96.17% of material experts were described as